Paradigm for the development of a lanna music curriculum in Higher Education in Northern Thailand - Khanithep Pitupumnak (2018)
© 2018, Malaysian Journal of Music. This article reviews the status of Lanna music in higher education, offering suggestions for the development of Lanna music in Northern Thai universities. The researcher adopts a phenomenological method, utilising data from a number of interviews (N=20) and observations. The results suggest that Lanna music in higher education plays a significant role in shaping the cultural identity of the community. This unique style of music is often taught as a core area of study, as an extension to existing music curricula, or is being offered elsewhere as a general subject of study pursued by non-music students. In the development of Lanna music curricula, the main objective is to sustain musical traditions, musical creativity and to promote professionalism in performance. The curriculum needs to consider the readiness of the elements, especially those pertaining to culture and community, which form the foundation of knowledge. The curriculum should develop learners on the basis of their interests and potentials and promote a local program which is attentive to local contexts. Finally, the curriculum should consider the diversity of culture and needs of the community.